EFFICACY OF ADJUVANT CHEMOTHERAPY WITH OXALIPLATIN AND 5-FLUOROURACIL IN STAGE II-III GASTRIC CANCER PATIENTS AT THANH HOA ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes and adverse effects of the adjuvant Oxaliplatin – 5FU regimen in stage II–III gastric cancer patients at Thanh Hoa Oncology Hospital. Patients and Methods: A retrospective descriptive study was conducted on 45 patients with stage II–III gastric cancer who underwent radical surgery followed by adjuvant Oxaliplatin – 5FU chemotherapy from January 2022 to August 2025 at Thanh Hoa Oncology Hospital. Results: The mean study period was 23 ± 7.89 months. The 3-year overall survival (OS) rate was 73.1%, with a mean overall survival time of 34.63 ± 1.47 months. The 3-year disease-free survival (DFS) rate was 54.7%, with a mean disease-free survival time of 30.87 ± 1.80 months. Adverse effects were predominantly grades 1–2. Conclusion: The adjuvant Oxaliplatin – 5FU regimen for stage II–III gastric cancer at Thanh Hoa Oncology Hospital is safe and effective.
Keywords: Stage II–III gastric cancer; Adjuvant chemotherapy; Oxaliplatin – 5FU.